Sero-surveillance and sero-monitoring of locally produced PPR vaccine in the field and experimental level - Kabir, Md Ehsanul; Hossain, Md Mokbul; Ershaduzzaman, Md; Yousuf, Md Abu; Islam, Md Rafiqul (Asian Journal of Medical and Biological Research, 2016)
<!–[if gte mso 9]> ismail - [2010] 11.5606 <![endif]–> Peste des Petits Ruminants (PPR) is a highly contagious, economically important viral disease of goats with high morbidity and mortality. To control the disease effectively a live attenuated vaccine is available in Bangladesh which is produced by Livestock Research Institute (LRI), Mohakhali, Dhaka. The study was carried out to determine the immune status and immune response against PPR in field and experimental Black Bengal goats. Sero-surveillance of PPR was conducted by using c-ELISA in non-vaccinated 240 goats in Gazipur, Sirajgonj and Barisal. Out of the 240 goats tested, of which only 39 (20.31%) goats had positive level of PPR antibodies while 16.25% (13 out of 80 goats) in Gazipur, 28.75% (23 out of 80 goats) in Barisal and 3.75% ((3 out of 80 goats)) in Sirajgonj. In case of sero-monitoring of PPR, the result revealed that vaccinated goats from Rajshahi showed high positive result and have higher seroprevalence where 75% (60 out of 80 goats) were seropositive and only 25% (20 out of 80 goats) are seronegative. These result indicated that vaccinated Rajshahi goats is more resistant for PPR virus than non vaccinated goats. In experimentally to perform sero-monitoring, 10 seronegative goats were selected and divided into two equal groups (A and B).The immunization study against PPR with a commercial PPR vaccine was conducted on 5 goats of group A by inoculating @ 1.0 ml vaccine / animal subcutaneously and group B kept as non-vaccinated. The antibody titres against PPR in goats were determined at 0 day on vaccination and after 21DPV, 180DPV and 365DPV. The results found that 100% (5 out 5goats) seronegative in both vaccinated goats of group A and non-vaccinated goats of group B at 0 day on vaccination. The mean negative titres± SD were 79.285±13.921 and 76.707±9.265 in vaccinated group A and group B, respectively. The mean positive titers ±SD were 20.201±2.480, 8.630±4.970 and 11.382±1.419 at 21DPV, 180DPV an 365DPV, respectively in group A (100% seropositive). In case of non-vaccinated group B, the mean negative titres±SD were 74.258±7.793, 77.726±9.142 and 82.965±7.492 at 21DPV, 180DPV and 365DPV, respectively (100% seronegative). As it is observed, the antibody titres remain at the level over the period of time that indicates the immune response against PPR. From this finding, it is said that PPR vaccine could produce immune response in goats for about one year or 365 days. Asian J. Med. Biol. Res. March 2016, 2(1): 33-37 <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>